Egypt’s Haya Karima Initiative: An assessment of its rural and economywide impacts - Raouf, Mariam; Kurdi, Sikandra; Cicowiez, Martin; Lofgren, Hans; Yassa, Basma; Kamaly, Ahmed; Helmy, Gamel (International Food Policy Research Institute, 2023)
Egypt’s Haya Karima (HK) Initiative aims at improving the quality of life in the country’s rural communities through interventions related to human development, infrastructure, and economic sectors. This presidential initiative, whose name translates to “Decent Life” in English, has four strategic goals, all targeting Egypt’s rural population: building human capital, improving quality of life, improving the standard of living for the most vulnerable, and providing decent and productive job opportunities. The initiative is aligned with the UN Sustainable Development Goals (SDGs) and the objectives of Egypt Vision 2030. HK aims to not only curb material poverty but also multidimensional poverty by expanding the umbrella of comprehensive social protection, with a focus on education, health, infrastructure, and employment. It also focuses on achieving the goal of geographical equity by addressing regional disparities that affect rural areas such as Upper Egypt. Here, we describe a recently completed study that assesses the economywide effects of the first phase of HK. The analysis was done by the International Food Policy Research Institute (IFPRI), in collaboration with Egypt’s Ministry of Economic Planning and Development (MPED) under the project Evaluating Impact and Building Capacity (EIBC), funded by the United States Agency for International Development (USAID).